2022
DOI: 10.26858/ijole.v6i2.21511
|View full text |Cite
|
Sign up to set email alerts
|

EFL Slow Learners’ Perception in Speaking with Authentic Multimedia Assisted Language Learning

Abstract: The proliferation of assisted technology has been widely used in language learning, but this should be able to accommodate inclusive language learning which has become an important issue in today’s English language teaching and the higher education landscape in Indonesia. This study examined the perception of EFL slow learners in terms of the integration of an inclusive technology with authentic multimedia assisted language learning (AMALL). It discovered the impact of authentic multimedia assisted language le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…One of the most interesting parts of the multicultural and technological themes is that they come from different institutions across the globe such as El Khairat (2021); Sakkir et al (2021); Mahadini et al (2021); Apriyanti et al (2021); Wen et al, (2021). The second reason is that multicultural themes appear to be one of the most interesting categories for authors because it covers different ranges of ideas and discourses in the area of language education and technology such as ; Alkhanani (2022); Nindya et al (2022); Abduh, Sakkir et al (2022); Further reason is that multicultural themes become the iconic perceived ideas of the language editors since the transdisciplinary and multidisciplinary lens of science and technology such as Yulian et al (2022); ; Suwastini et al, (2023).…”
Section: Discussionmentioning
confidence: 99%
“…One of the most interesting parts of the multicultural and technological themes is that they come from different institutions across the globe such as El Khairat (2021); Sakkir et al (2021); Mahadini et al (2021); Apriyanti et al (2021); Wen et al, (2021). The second reason is that multicultural themes appear to be one of the most interesting categories for authors because it covers different ranges of ideas and discourses in the area of language education and technology such as ; Alkhanani (2022); Nindya et al (2022); Abduh, Sakkir et al (2022); Further reason is that multicultural themes become the iconic perceived ideas of the language editors since the transdisciplinary and multidisciplinary lens of science and technology such as Yulian et al (2022); ; Suwastini et al, (2023).…”
Section: Discussionmentioning
confidence: 99%
“…This final instructional modality being examined has the most relevant research that met the study's criteria (Fouz-Gonzalez, 2017;Fouz-Gonzalez, 2020;Kusnaryani et al, 2019;Nanjundan et al, 2020;Sherine et al, 2019;Yin, 2019;Yulian, 2022). Thus, seven studies were found that explored the instructional modality of Mobile Assisted Language Learning.…”
Section: Mall: Mobile Assisted Language Learningmentioning
confidence: 99%